Vincent and John Jim Cornect play some music - Thomas, Gerald (1973)
Vincent Cornect joue la guitare et John Jim Cornect joue le violon. Ils jouent du bluegrass et puis Jim Hodder arrive. Tout le monde est présenté et puis ils jouent de la musique et se causent un peu. -- Vincent Cornect plays guitar and John Jim Cornect plays violin. They play a few songs and then play some blue-grass and then Jim Hodder arrives and introductions are made. They play music and have a chat.